Dynamic of cold-atom tips in anharmonic potentials - Menold, Tobias; Federsel, Peter; Rogulj, Carola; Hölscher, Hendrik; Fortágh, József; Günther, Andreas (Beilstein Journal of Nanotechnology, 2016)
Background: Understanding the dynamics of ultracold quantum gases in an anharmonic potential is essential for applications in the new field of cold-atom scanning probe microscopy. Therein, cold atomic ensembles are used as sensitive probe tips to investigate nanostructured surfaces and surface-near potentials, which typically cause anharmonic tip motion.Results: Besides a theoretical description of this anharmonic tip motion, we introduce a novel method for detecting the cold-atom tip dynamics in situ and real time. In agreement with theory, the first measurements show that particle interactions and anharmonic motion have a significant impact on the tip dynamics.Conclusion: Our findings will be crucial for the realization of high-sensitivity force spectroscopy with cold-atom tips and could possibly allow for the development of advanced spectroscopic techniques such as Q-control.
Keywords: anharmonic motion; cold-atom scanning probe microscopy; dephasing; dynamic mode; tip oscillation